Los programas infantiles violentos que se transmiten en la televisión y su incidencia en el comportamiento agresivo de los niños y niñas de primer año de educación básica de la unidad educativa “República de México”, de la parroquia Cordoncillo del cantón Atahualpa, provincia del Oro. período lectivo 2014-2015. Lineamientos alternativos - Aguilar Tinoco, Karen Madelayne (2015)
This current thesis is aimed to investigate the following topic: Violent children programs are broadcast on television aad its impact or the aggressive behavior in children in first grade of elementary School of the Republic of Mexico School, of Cordoncillo parish Atahualpa canton, El Oro province 2014-2015 academic year. Alternative guidelines. The problematic Research Center led me to investigate in what way the violent children's programs broadcast on television influence aggressive behavior of children and primer Girls Basic Education year ?.The general objective of the current research is determine how violent children’s programs are broadcast on television influence on the aggressive behavior in children in first grade. Methods used to the preparation of this research were scientific, deductive, inductive, analytical, synthetic, and descriptive. They allowed for discussion and comparison of the proposed variables. Two instruments were applied: A survey of parents to identify television programs with violent, demostrations and a observation sheet applied to children in first grade, to assess and determine the aggressive behavior in the classroom, as well as 6 aspects of social, behavior of children. The objectives and results of this research allowed to draw the conclusion that violent children’s programs broadcast on television do affect aggressive behavior in children. In first grade. As a researcher recommends that teachers make conversations with parents to sensitize their children not watch too much television and also they should choose educational programs that help their children have good behavior in society